Twenty-five years of Living Under Contract: Contract farming and agrarian change in the developing world - Vicol, Mark; Fold, Niels; Hambloch, Caroline; Narayanan, Sudha; Niño, Helena Pérez (Wiley, 2022)
The expansion of contract farming schemes through regions of the developing world in the era of the globalization of agriculture raises questions that are central to the study of agrarian political economy. Contract farming has extended the footprint of commodity production and integrated land and labour not otherwise captured in forms of direct production and marketing. 25 years after the publication of Living Under Contract: Contract Farming and Agrarian Transformation in Sub-Saharan Africa, a foundational collection edited by Peter Little and Michael Watts, it is necessary to take stock of the most prominent developments in the practice of contract farming and in the political economy literature studying it. The ultimate contribution of Living Under Contract was framing contract farming as expressing the unevenness of power relations in agriculture and grounding it in specific political, historical and social contexts that were not examined in the mainstream accounts. This introduction to the special issue revisits the questions that have remained relevant or re-emerged in the political economy literature on contract farming; it raises new questions that reflect contemporary developments and it explains how the papers in this collection contribute to the expansion of the theoretical and empirical horizons of the research on contemporary contract farming in low and middle-income countries.